Response to Selenium by Callus Cultures Derived from Astragalus Species - Ziebur, Nancy K. (1971)
Callus cultures were obtained from five selenium accumulator and three nonaccumulator species of Astragalus. Their morphological characteristics and their growth responses to light, sucrose, kinetin, and 2,4-dichlorophenoxyacetic acid are described. Calluses derived from accumulator species characteristically retained their tolerance to high concentrations of selenate and selenite, whereas calluses derived from nonaccumulator species were markedly inhibited by these two forms of selenium. Competition between sulfate and selenate was demonstrated. The two types of calluses could not be distinguished on the basis of (75)Se-labeled selenate or selenite uptake. Neutron activation analysis failed to show differences in selenium content between the two types of calluses grown on media to which no selenium had been added.